Tinder Sebagai Platform Pencarian Jodoh di Zaman Digital - Prima, Cinthya Fatama; Suarsana, I Nyoman; Wiasti, Ni Made (Humanis; Vol 25 No 3 (2021), 2021)
The phenomenon of dating applications is increasingly growing in society. This is evidenced by the rise of dating applications. Tinder is one of the most talked about dating apps. Tinder brings people a change in the way it is social. Since Tinder was launched, now humans can easily make new friends virtually. Dating applications are believed to be able to provide a solution when a match comes for its users. This is what attracts researchers to dig deeper into the phenomenon of matchmaking through the Tinder application as a matchmaking platform in the digital era. The theory used by the researcher is social action theory and theory of love by Wheel theory. This research also uses a qualitative descriptive method and a qualitative approach. The results show that the resource person uses the Tinder application to find new friends, girlfriends and even husbands / wives. The researcher concluded that the actions taken by the informants on average had the same answer. This action is done for the purpose of finding a new socials circle.